2021
DOI: 10.1002/humu.24278
|View full text |Cite
|
Sign up to set email alerts
|

Actionable genomic variants in 6045 participants from the Qatar Genome Program

Abstract: In a clinical setting, DNA sequencing can uncover findings unrelated to the purpose of genetic evaluation. The American College of Medical Genetics and Genomics (ACMG) recommends the evaluation and reporting of 59 genes from clinic genomic sequencing. While the prevalence of secondary findings is available from large population studies, these data lack Arab and other Middle Eastern populations. The Qatar Genome Program (QGP) generates whole-genome sequencing (WGS) data and combines it with phenotypic informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…Recently, we have reported a total of 60 pathogenic and likely pathogenic variants in 25 ACMG genes in 141 unique individuals (Elfatih et al, 2021) and several other efforts are currently under way to build the catalogs of predicted loss‐of‐function variants and Mendelian disorders mutations and to characterize the pharmacogenomic (Jithesh et al, 2022) and the cancer landscapes of the Qatari population (Saad et al, in press). Furthermore, using a combination of whole genomes and exome sequence data and clinical reports, we developed a microarray with Qatari‐specific pathogenic variants that could be used to rapidly, accurately and at low cost, screen the Qatari population for pathogenic variants of newborns, premarital couples, and patients presenting to the clinic (Rodriguez‐Flores, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have reported a total of 60 pathogenic and likely pathogenic variants in 25 ACMG genes in 141 unique individuals (Elfatih et al, 2021) and several other efforts are currently under way to build the catalogs of predicted loss‐of‐function variants and Mendelian disorders mutations and to characterize the pharmacogenomic (Jithesh et al, 2022) and the cancer landscapes of the Qatari population (Saad et al, in press). Furthermore, using a combination of whole genomes and exome sequence data and clinical reports, we developed a microarray with Qatari‐specific pathogenic variants that could be used to rapidly, accurately and at low cost, screen the Qatari population for pathogenic variants of newborns, premarital couples, and patients presenting to the clinic (Rodriguez‐Flores, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Qatar Biobank (QBB) is a population study that includes adult Qatari nationals and long-term residents (≥15 years living in Qatar) [34,35]. QBB samples and data have been used in multiple genetic studies [19,[36][37][38].…”
Section: Study Populationmentioning
confidence: 99%
“…We identified 17 mutations, characterized in the literature as pathogenic, out of which 16 were located in LDLR. Notably, 6 of these variants in LDLR were previously reported in ~6000 subjects from Qatar but without any phenotypic associations with FH (Elfatih et al, 2021). In contrast, some of these 16 variants we identified have been directly associated with FH phenotypes in other populations.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, accumulating studies have also explored the genetic spectrum of FH in the wider Middle Eastern region (Awan et al, 2019), with reports of mutations occurring predominantly in LDLR (Alhababi and Zayed, 2018). Notably, a recent study reported mutations in 6 LDLR variants in a subset of ~6,000 individuals from Qatar, but no phenotypic analyses or evidence were sought for FH (Elfatih et al, 2021). Moreover, GWAS have also linked specific lipid risk variants to various populations in the region (Hebbar et al, 2019), specifically in Qatar (Thareja et al, 2021).…”
Section: Introductionmentioning
confidence: 99%